Mutations Selected After Exposure to Bacteriocin Lcn972 Activate a Bce-Like Bacitracin Resistance Module in Lactococcus lactis - Campelo, Ana Belén; López-González, María Jesús; Escobedo, Susana; Janzen, Thomas; Neves, Ana Rute; Rodríguez, Ana; Martínez, Beatriz (Frontiers in Microbiology, 2020)
Resistance against antimicrobial peptides (AMPs) is often mediated by detoxification modules that rely on sensing the AMP through a BceAB-like ATP-binding cassette (ABC) transporter that subsequently activates a cognate two component system (TCS) to mount the cell response. Here, the Lactococcus lactis ABC transporter YsaDCB is shown to constitute, together with TCS-G, a detoxification module that protects L. lactis against bacitracin and the bacteriocin Lcn972, both AMPs that inhibit cell wall biosynthesis. Initially, increased expression of ysaDCB was detected by RT-qPCR in three L. lactis resistant to Lcn972, two of which were also resistant to bacitracin. These mutants shared, among others, single point mutations in ysaB coding for the putative Bce-like permease. These results led us to investigate the function of YsaDCB ABC-transporter and study the impact of these mutations. Expression in trans of ysaDCB in L. lactis NZ9000, a strain that lacks a functional detoxification module, enhanced resistance to both AMPs, demonstrating its role as a resistance factor in L. lactis. When the three different ysaB alleles from the mutants were expressed, all of them outperformed the wild-type transporter in resistance against Lcn972 but not against bacitracin, suggesting a distinct mode of protection against each AMP. Moreover, PysaD promoter fusions, designed to measure the activation of the detoxification module, revealed that the ysaB mutations unlock transcriptional control by the TCS-G, resulting in constitutive expression of the ysaDCB operon. Finally, deletion of ysaD was also performed to get an insight into the function of this gene. ysaD encodes a secreted peptide and is part of the ysaDCB operon. YsaD appears to modulate signal relay between the ABC transporter and TCS-G, based on the different response of the PysaD promoter fusions when it is not present. Altogether, the results underscore the unique features of this lactococcal detoxification module that warrant further research to advance in our overall understanding of these important resistance factors in bacteria.